Analisis Muraa’t Al-Nadzir pada Surah Ar-Rahman (Study Analisis Ilmu Badi’) - Dea Adinda; Syarifah Aulia; Harun Al Rasyid (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research aims to examine the use of the Muro'at al-Nazhir concept in the science of balaghah which is applied to Surah Ar-Rahman in the Al-Qur'an. Muro'at al-Nazhir is a rhetorical technique that emphasizes harmony in meaning, sound, structure, and even contrast of meaning in a text, thereby creating beauty and strengthening the message. Through a text analysis approach, this research identifies various forms of Muro'at al-Nazhir contained in Surah Ar-Rahman, including sound harmony through the repetition of the phrase